A2.15 Ra phenotype at presentation differs among patients with few versus many autoantibodies. (24th February 2016) - Derksen, VFAM; Ajeganova, S; van der Helm-van Mil, AHM; Hafström, I; Huizinga, TWJ; Toes, REM; Trouw, LA; Svensson, B; van der Woude, D
Abstract : Background and objectives: Patients with rheumatoid arthritis (RA) are frequently positive for one or several autoantibodies like rheumatoid factor (RF), anti-citrullinated protein antibodies (ACPA) and anti-carbamylated protein antibodies (Anti-CarP). The number of autoantibodies can be seen as a proxy for the breadth of the (humoral) autoimmune response. Seropositive and seronegative patients differ in respect to underlying risk factors and disease outcome. However, it is unclear whether seropositive and seronegative patients differ at presentation, and if disease presentation is affected by the number of autoantibodies present. Therefore, this study investigated this association. Materials and methods: Two independent cohorts of early RA patients were analysed: Leiden Early Arthritis Cohort (EAC) (n = 845), and the Swedish BARFOT (Better Anti-rheumatic Farmaco-therapy) study (n = 805). All patients fulfilled the 1987 ACR criteria and had a short symptom duration (EAC < 24 months, BARFOT < 12 months). Autoantibody status was determined at baseline. Commercial agglutination tests were used to measure RF in BARFOT. Commercial enzyme linked immunosorbent assays (ELISAs) were used to measure RF in EAC and anti-CCP2 in both cohorts. Antibodies against carbamylated fetal calf serum were measured for both cohorts in Leiden using in-house ELISAs. Ordinal regression investigating the association between baseline characteristics and the number of autoantibodies was performed to calculate odds ratios (ORs) and 95% confidence intervals (CI). To study independent associations, variables with a univariate p < 0.10 were included in a multivariate model. Results: The distribution of the number of autoantibodies in both cohorts was similar (EAC (0:31%, 1:17%, 2:17%, 3:35%) and BARFOT (0:33%, 1:14%, 2:24%, 3:29%)). In multivariate analysis in both cohorts, patients with more RA-associated antibodies were younger (OR(95% CI) per 10 years: EAC 0.89(0.80–0.98), BARFOT 0.87(0.79–0.95)), more often smokers (OR(95% CI): EAC 1.61(1.19–2.16), BARFOT 1.59(1.20–2.11)), had a longer symptom duration (OR(95% CI) per 3 months: EAC 1.11(1.01–1.22), BARFOT 1.25(1.09–1.43)) and a higher ESR (OR(95% CI) per 10 mm/hour: EAC 1.11 (1.05–1.18), BARFOT 1.20(1.12–1.30)) at presentation compared to patients with fewer autoantibodies. Conclusions: The number of autoantibodies is associates with differences in several phenotypic characteristics at presentation, indicating that the breadth of the (humoral) autoimmune response affects the initial clinical presentation of RA.